1993
DOI: 10.1002/1097-0142(19930615)71:12<3920::aid-cncr2820711220>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography with fluorine-18-deoxyglucose in the detection and staging of breast cancer

Abstract: Background. An increasing number of patients with breast cancer is being treated with preoperative chemotherapy. Evaluation of treatment response may be facilitated by positron emission tomography (PET) with 18F‐fluoro‐2‐deoxy‐D‐glucose (FDG). This noninvasive technique may allow prediction of the chemotherapy outcome in an early phase of the treatment. Methods. Prerequisites for treatment monitoring with PET are good FDG uptake in the tumor, high specificity, and a reliable quantification technique. These fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
1
6

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(62 citation statements)
references
References 13 publications
1
54
1
6
Order By: Relevance
“…In the study by Wahl et al (1991), ten out of ten primary tumours were visualized and FDG scanning was reliable in the detection of lymph node and distant metastases. Nieweg et al (1993), found that monitoring treatment with PET FDG in 10 out of 11 patients with primary breast cancer the tumour was visualized. In all five patients with increased uptake in the lymph nodes, pathological proof of metastatic cancer was found.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Wahl et al (1991), ten out of ten primary tumours were visualized and FDG scanning was reliable in the detection of lymph node and distant metastases. Nieweg et al (1993), found that monitoring treatment with PET FDG in 10 out of 11 patients with primary breast cancer the tumour was visualized. In all five patients with increased uptake in the lymph nodes, pathological proof of metastatic cancer was found.…”
Section: Discussionmentioning
confidence: 99%
“…Using a whole-body imaging technique, Hoh et al [83] detected 15/17 primary breast carcinomas. Nieweg et al [249,250] identified 10/11 primary lesions. Adler et al [251,252], in a prospective study, recognized 26/27 malignant lesions.…”
Section: Breast Cancermentioning
confidence: 99%
“…Available data point to the value of PET in this indication but it has not yet been tested in specific patient groups, such as patients with stage III breast cancer at the time of initial diagnosis, or later on in the disease, eog. in patients with suspected recurrences [246,249,250,259].…”
Section: Breast Cancermentioning
confidence: 99%
“…Use of fluorine-18 fluorodeoxyglucose ( 18 F-FDG) and positron emission tomography (PET) has also been evaluated for the detection of breast cancer [14][15][16][17][18][19][20][21]. In a larger patient group, Avril et al reported a sensitivity and specificity for the detection of primary breast cancer of 88% and 78%, respectively [18].…”
Section: Histopathologymentioning
confidence: 99%